Pemanfaatan Limbah Batang Pisang Melalui Pelatihan Pembuatan Pupuk Organik Cair pada Masyarakat Desa Purworejo Kabupaten Blitar - Muhammad Helmi Hakim; Muhammad Febri Alfa Rizki; Alfian Perdana Zahri; Milya Nur Fadila; Muhammad Fikri Aziz Mustofa; Mohamad Faisal Burhani Pradana; Atina Ilma (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Purworejo Village is one of the villages in Sanankulon District, Blitar Regency, East Java Province. Purworejo Village has natural wealth in the form of banana plantations managed by the Wijaya Kusuma Community Group. This banana plantation produces organic agricultural waste in the form of banana stems. Banana stems that accumulate and are not processed for too long will cause an unpleasant odor, and have not been utilized because of the lack of residents related to processing banana tree stump as Liquid Organic Fertilizer. One alternative that can be taken is that banana stems can be processed into Liquid Organic Fertilizer using the help of a decomposer or Local Micro Organisms as a decomposer of solid organic matter into liquid. From this alternative, it is hoped that banana stem waste can be minimized properly. In addition, it can also create new jobs for the people of Purworejo Village, thus helping to increase the income of the people in Purworejo Village. In this PHP2D activity, the community was given hands-on training and practice. There are several activities that include the presentation of materials, and the practice of making Liquid Organic Fertilizer by the PHP2D Himafis UNU Blitar Team to the people of Purworejo Village